Basic pharmacology for nurses - Clayton, Bruce D.; Willihnganz, Michelle (St. Louis, Missouri : Elsevier, Mosby, 2013)
"Basic Pharmacology for Nurses is a modern classic nursing pharmacology textbook known for its impeccably accurate drug content and its practical applications of the nursing process. A consistent emphasis on health promotion through monitoring and patient education is a hallmark of the book. Introductory units ground the reader in basic principles of pharmacology and medication administration. Subsequent body-system units apply the nursing process to every major disorder, and appropriate nursing implications are discussed for every drug class to promote safe medication administration."--Publisher's website
Unit 1: Foundations of Pharmacology -- Unit 2: Illustrated Atlas of Medication Administration and Math Review -- Unit 3: Drugs That Affect the Autonomic and Central Nervous Systems -- Unit 4: Drugs That Affect the Cardiovascular System -- Unit 5: Drugs Used to Treat Disorders of the Respiratory System -- Unit 6: Drugs That Affect the Digestive System -- Unit 7: Drugs That Affect the Endocrine System -- Unit 8: Drugs That Affect the Reproductive System -- Unit 9: Drugs That Affect Other Body System -- Unit 10: Drugs That Affect the General Health of the Body
Includes bibliographical references and index.
Keywords: DRUGS -- DOSAGE